Additional file 1 of High prevalence, intensity, and genetic diversity of Trichinella spp. in wolverine (Gulo gulo) from Yukon, Canada - Rajnish Sharma (679635); N. Jane Harms (10273280); Piia M. Kukka (10273283); Thomas S. Jung (4431118); Sarah E. Parker (3039420); Sasha Ross (10273286); Peter Thompson (165468); Benjamin Rosenthal (10273289); Eric P. Hoberg (9735752); Emily J. Jenkins (10273292) (2021)
Additional file 1: Table S1. Prevalence of Trichinella spp. in wild carnivores in Canada and Alaska. Table S2. Prevalence and larval burden (larvae per gram) of Trichinella spp. in wolverine from different geographical locations.